Junior High School Students' Perception about the Computer-Based Examination aith Computer-Based Science Evaluation (CBSE) - Fahrurrohman, Atriyanto; Ridlo, Saiful; Nugroho, Sunyoto Eko (Journal of Innovative Science Education, 2019)
Computer-Based Science Evaluation (CBSE) is one of just my assessment for measuring student knowledge tailored to the ability. Based on observations in Surakarta Country 1 that MTs has still not implemented the computer as a tool in the evaluation of the learning process. As long as this is still using paper in performing the evaluation. The purpose of the study is to describe the student's perception of the computer-based examination with Computer-Based Science Evaluation (CBSE). Place research at MTs Country, Surakarta Class VII 1 school year 2017/2018. Methods used i.e. descriptive – qualitative data collection techniques include documentation, interviews, observation, and question form. Data is already collected data triangulation method is done next. Results of the study i.e. score student perception of the use of CBSE demonstrated by feasibility question good, the feasibility of CBSE media very well, and the effectiveness of the CBSE is very good. The opinions of the students against the use of CBSE i.e. attractive, happy to use it, it's easy to understand the problem, the only difficulty in working on the problem.  This research is expected to be the experience for students working on an online-based exam, as well as input for teachers and schools to implement an online-based exam in measuring students ' ability after carrying out the learning process. The use of the CBSE is expected to be used in Deuteronomy daily (UH), Deut. midterm (UTS), a repeat of the end of the semester (UAS).